A redox‐active polythiophene‐modified separator for safety control of lithium‐ion batteries. Issue 20 (7th August 2013) - Zhang, Haiyan; Cao, Yuliang; Yang, Hanxi; Lu, Shigang; Ai, Xinping
ABSTRACT A potential‐sensitive separator is prepared simply by incorporating a redox‐active poly(3‐butylthiophene) (P3BT) into the micropores of a commercial porous polyolefin film and tested for overcharge protection of LiFePO4/Li4Ti5O12 lithium‐ion batteries. The experimental results demonstrate that owing to the reversible p‐doping and dedoping of the redox‐active P3BT polymer embedded in the separator with the changes of the cathode potential from an overcharge state to a normal operating state, this type of separator can reversibly switch between electronically insulating state and conductive state to maintain the charge voltage of LiFePO4/Li4Ti5O12 cells at a safety value of ≤2.4 V, and thus protecting the cell from voltage runaway. As this type of the separators works reversibly and has no negative impact on the battery performances, it can be used as an internal and self‐protecting mechanism for commercial lithium‐ion batteries and other rechargeable batteries. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1487–1493